DEPENDENCE OF THE SPECKLE-PATTERNS SIZE AND THEIR CONTRAST ON THE BIOPHYSICAL AND STRUCTURAL PARAMETERS OF BIOLOGICAL TISSUES - N. D. Abramovich; S. K. Dick (Приборы и методы измерений)
Speckle fields are widely used in optical diagnostics of biotissues and evaluation of the functional state of bioobjects. The speckle field is formed by laser radiation scattered from the object under study. It bears information about the average dimensions of the scatterers, the degree of surface roughness makes it possible to judge the structural and biophysical characteristics of individual tissue cells (particles), on the one hand, and the integral optical characteristics of the entire biological tissue. The aim of the study was – the determination of connections between the biophysical and structural characteristics of the biotissue and the light fields inside the biotissues.The model developed of the medium gives a direct relationship between the optical and biophysical parameters of the biotissue. Calculations were carried out using known solutions of the radiation transfer equation, taking into account the multilayer structure of the tissue, multiple scattering in the medium, and multiple reflection of irradiation between the layers.With the increase wavelength, the size of speckles formed by the non-scattered component (direct light) of laser radiation increases by a factor of 2 from 400 to 800 μm in the stratum corneum and 5 times from 0.6 to 3 μm for the epidermis and from 0.27 to 1.4 μm to the dermis. Typical values of sizes of speckles formed by the diffraction component of laser radiation for the stratum corneum and epidermis range from 0.02 to 0.15 μm. For the dermis typical spot sizes are up to 0.03 μm. The speckle-spot size of the diffusion component in the dermis can vary from ±10 % at 400 nm and up to ±23 % for 800 nm when the volume concentration of blood capillaries changes. Characteristic dependencies are obtained and biophysical factors associated with the volume concentration of blood and the degree of it’s oxygenation that affect the contrast of the speckle structure in the dermis are discussed.The of speckles׳ size in the layers of tissue varies from a share of micrometer to millimeter. The established dependence makes it possible to determine the depth of penetration of light into the biotissue based on the dimensions of speckles. Calculation of the contrast of the speckle structure of scattered light in visible spectral range at different depths in the biotissue made it possible to establish the dependence of the contrast value of the interference pattern on the degree of oxygenation of the blood and the volume concentration of capillaries in the dermis.